2012
DOI: 10.1186/1550-2783-9-7
|View full text |Cite|
|
Sign up to set email alerts
|

The influence of a CYP1A2 polymorphism on the ergogenic effects of caffeine

Abstract: Background: Although caffeine supplementation improves performance, the ergogenic effect is variable. The cause(s) of this variability are unknown. A (C/A) single nucleotide polymorphism at intron 1 of the cytochrome P450 (CYP1A2) gene influences caffeine metabolism and clinical outcomes from caffeine ingestion. The purpose of this study was to determine if this polymorphism influences the ergogenic effect of caffeine supplementation. Methods: Thirty-five trained male cyclists (age = 25.0 ± 7.3 yrs, height = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
165
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(190 citation statements)
references
References 17 publications
(33 reference statements)
9
165
2
1
Order By: Relevance
“…Nevertheless, the fact that there were significant differences in the data suggests some meaningful findings that can be further explored in the future using larger sample sizes. Furthermore, inherent in caffeine-supplementation trials is the contribution of the individual response to caffeine, which involves genetics, habituation levels and withdrawal effects (Sökmen et al, 2008;Womack et al, 2012). It is also worth noting that response bias cannot be entirely discounted, as 9 out of 10 participants correctly guessed which trial they were in.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, the fact that there were significant differences in the data suggests some meaningful findings that can be further explored in the future using larger sample sizes. Furthermore, inherent in caffeine-supplementation trials is the contribution of the individual response to caffeine, which involves genetics, habituation levels and withdrawal effects (Sökmen et al, 2008;Womack et al, 2012). It is also worth noting that response bias cannot be entirely discounted, as 9 out of 10 participants correctly guessed which trial they were in.…”
Section: Discussionmentioning
confidence: 98%
“…Only one study included in the present review conducted genetic analysis pertaining to caffeine metabolism [57]. Womack et al [57] tested participants' CYP1A2 genotype and reported that fast metabolisers of caffeine (A/A) performed better in a 40 km cycle time-trial following caffeine ingestion compared to slow metabolisers of caffeine (A/C and C/C).…”
Section: Discussionmentioning
confidence: 99%
“…Womack et al [57] tested participants' CYP1A2 genotype and reported that fast metabolisers of caffeine (A/A) performed better in a 40 km cycle time-trial following caffeine ingestion compared to slow metabolisers of caffeine (A/C and C/C). However, more research is needed to determine the effects of CYP1A2 genotype on the ergogenicity of caffeine as well as controlling for confounding variables such as other genetic factors (ADORA2A) and epigenetic factors such as, age, smoking, gender and ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Four of these studies used a caffeine dosage of 6 mg/kg of body weight 5,[18][19][20] , two studies used a caffeine dosage of 3 mg/kg of body weight 21,4 and one study used an intake fixed dose of 200 mg of caffeine (~2.5 mg/kg of body weight) 22 . Desbrow et al 18 and Irwin et al 4 evaluated the shortest time to reach a target amount of work among cyclists.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…Desbrow et al 18 and Irwin et al 4 evaluated the shortest time to reach a target amount of work among cyclists. Bortolotti et al 5 and Acker-Hewitt et al 21 applied a distance of 20 km, whereas Spence et al 22 , Skinner et al 20 and Womack et al 19 used a distance of 40 km. The studies showed an improvement in time trial performance among the subjects who ingested caffeine (effect size= -0.40, p< 0.01, interpretation: small; Figure 4).…”
Section: Description Of the Included Studiesmentioning
confidence: 99%